Association between Clinical Frailty Scale and mortality 24 months after hospitalisation in adult patients with COVID-19 - Julia Minnema; Melvin Lafeber; Roos S.G. Sablerolles; Janneke A.L. van Kempen; Lisanne Tap; Harmke A. Polinder-Bos; Bob P.A. van de Loo; Hugo van der Kuy; Miriam C. Faes; Jacomien Aleman; Jos Tournoy; Lorenz Van der Linden; et al. (Heliyon)
Background: The clinical frailty scale (CFS) was used as a triage tool for medical decision making during the COVID-19 pandemic. The CFS has been posed as a suitable risk marker for in-hospital mortality in COVID-19 patients. We evaluated whether the CFS is associated with mortality 24 months after hospitalisation for COVID-19. Methods: The COvid MEdicaTion (COMET) study is an international, multicentre, observational cohort study, including adult patients hospitalised for COVID-19 between March 2020–July 2020. Patients’ characteristics, prescribed medication, clinical characteristics, and CFS were collected at admission, survival data were collected 24 months after hospitalisation. Multivariable cox proportional hazard models stratified by age (<65 and ≥65 years), and adjusted for covariates (age, sex, number of drugs, and types of drug class as a proxy for comorbidities) were used to study the association between the CFS and 24-month mortality after hospitalisation. Results: In this study, 1238 fit (CFS 1–3), 478 mildly frail (CFS 4–5), and 235 frail (CFS 6–9) patients were included for baseline analysis (median age 68 years (IQR 58–78); 58.5 % male). Frailty was associated with an increased risk of 24-month mortality after hospitalisation in older patients (HR 1.91, 95 % CI [1.17–3.12]), in younger adults a trend was seen (HR 3.13, 95 % CI [0.86–11.36]). Conclusion: The results suggest that the CFS is an indicator for mortality 24 months after hospitalisation in COVID-19 patients.